Problems of a modern guide: Mission, profession, certification - Olga A. Staina; Rita B. Khusanova (Управление культурой)
Relevance of the study. The Russian tourism industry has been actively developing in recent years, especially since 2021, when the country's government adopted the national project «Tourism and Hospitality Industry». The total cost of the national project «Tourism and Hospitality Industry» in 2025-2030 may amount to 3.56 trillion rubles in the baseline scenario. It is proposed to allocate 501.1 billion rubles from the federal budget for these purposes. Thus, the tourism sector is becoming more and more important both for the country's economy and for the development of individual regions. Moreover, tourism has a multiplier effect on all sectors of the economy. To fulfill the plans, professional personnel needed, first, «guides (guides)», because they are the «primary link» of the industry, according to which the impression of the excursionist's place of stay is formed. Problem. The profession of «tour guide (guide)» is in demand in the labor market. For the training of professional personnel, an education system has been created: from advanced training courses and professional training courses to training in higher educational organizations. However, problems with the quality of excursion services remain not fully resolved. Certification of guides is one of the conditions for improving the quality of tourist services, but certification is not a sufficient guarantee of quality. Objective. In this article, we will consider issues related to the activities of tour guides in the modern tourism industry. We will pay attention to the transforming requirements for excursion activities in connection with new sociocultural conditions, increasing consumer needs and problems associated with the certification of guides. Using the example of the Sverdlovsk region, we will consider issues related to the activities of professional communities, existing opportunities for improving the professional level and education of guides, as well as the necessary conditions for passing certification and the problems facing members of certification commissions. In the article, we will consider the opportunities for professional education and advanced training of a modern guide on the example of the Sverdlovsk region and the city of Ekaterinburg. Results and conclusions. It is necessary to solve the problem of training professional personnel in the field of tourism and hospitality by intensifying the work of all subjects related to the industry: authorized authorities, educational organizations, professional communities and the guides themselves.